Contribution to Ghana's Fish Farming Certification Protocol - CGIAR Research Program on Policies, Institutions, and Markets (2021)
This protocol developed by IFPRI and partners aims to increase farm productivity and ensure fish safety and quality. It is currently being validated by experts and stakeholders.